Grinding to produce polydopamine-modified polypyrrole nanotubes with enhanced performance for sodium-ion capacitor. (1st December 2022) - Wu, Xuena; Li, Zhan; Tian, Yan; Lu, Yanmin; Jiang, Haihui; Liu, Libin; Gai, Ligang
Highlights: Polypyrrole nanotubes (PNTs) are synthesized through a templating method. PNTs are featured with relatively uniform size, smooth surface, and high S BET . The electrochemical performance of PNTs is improved by a simple grinding method. Electron transfer from polydopamine to PNTs is evidenced by FT-IR and XPS results. PNT/PDA-10‖MnO2 device presents capacitance retention of 83.7% after 10, 000 cycles. Abstract: Conductive polymers have a great potential for application in electrochemical energy-storage systems (EES). However, the structural instability due to the swelling/shrinking of polymer chains during charge/discharge cycles hampers the wide use of conductive polymers in EES. In this paper, polypyrrole nanotubes (PNTs) are first produced by a methyl orange-templated method. The influence of the feeding sequence of reactants on the size, morphology, specific surface area, and conductivity of PNTs is explored. Second, a composite of polydopamine (PDA)-modified PNTs (PNT/PDA) is produced by grinding PNTs with dopamine hydrochloride (DAH) in N-methyl pyrrolidone. Dopamine in situ transforms into PDA modifier while PNTs are in situ doped by the hydrochloride. The effect of DAH/PNTs weight ratio on the electrode performance is investigated. The specific capacitance is doubled and the capacitance retention is increased by 26% for PNT/PDA after 1000 cycles at 1 A g –1, compared with pristine PNTs. Also, the asymmetric PNT/PDA‖MnO2 sodium-ion capacitor presents a capacitance retention of 83.7% after 10, 000 cycles with varying current densities in the range of 0.5–5 A g –1, higher than that of 70.5% for PNT-based counterpart. The enhanced electrochemical performance of PNT/PDA is attributed to the in situ acid doping and the electron transfer from PDA to PNTs due to the catecholic chemistry. Graphical abstract: Polypyrrole nanotubes (PNTs) are synthesized by mixing methyl orange (MO) and pyrrole first followed by addition of FeCl3 and, further, grinding PNTs with dopamine (DA) in N-methyl pyrrolidone, yielding PNT/PDA electrode with enhanced performance for sodium-ion capacitor. Image, graphical abstract